Distribution of Heavy Metals in Surface Sediments of the Bay of Bengal Coast - M. Z. H. Khan; M. R. Hasan; M. Khan; S. Aktar; K. Fatema (Journal of Toxicology)
The concentrations of major (Si, Al, Ca, Fe, and K) and minor (Cd, Mn, Ni, Pb, U, Zn, Co, Cr, As, Cu, Rb, Sr, and Zr,) elements in the surficial sediments were studied in an attempt to establish their concentration in the Bengal coast. It was revealed that the majority of the trace elements have been introduced into the Bengal marine from the riverine inflows that are also affected by the impact of industrial, ship breaking yard, gas production plant, and urban wastes. The concentration of heavy metals was measured using Atomic Absorption Spectroscopy and Energy Dispersive X-ray fluorescence instruments. The highest concentrations for several trace elements were thus recorded which generally decrease with distance from the coast. It was observed that the heavy metal concentrations in the sediments generally met the criteria of international marine sediment quality. However, both the contamination factor and pollution load index values suggested the elevation of some metals’ concentrations in the region. Constant monitoring of the Bengal coast water quality needs to be recorded with a view to minimizing the risk of health of the population and the detrimental impacts on the aquatic ecosystem.